The Behavioral Significance of Differing E EG Abnormalities in Children With Learning and/or Behavior Problems. - Tymchuk, Alexander J.; Knights, Robert M.; Hinton, George G. (Journal of Learning Disabilities, 1970)
The implications of EEG abnormalities in children with learning disabilities are considered. Groups of children with specific types of LEG abnormalities were compared on a variety of psychological tests. Paradoxical differences were found and these results were discussed. The EEG is of value only with other neurological data in evaluating specific neurological disorders.